PENERAPAN METODE MAKE A MATCH DISERTAI DENGAN MEDIA GOOGLE EARTH UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI PADA KOMPETENSI DASAR PROSES PEMBENTUKAN MUKA BUMI SISWA KELAS X-B MAN NGRAMBE KABUPATEN NGAWI TAHUN 2013/2014 - Nugraha, Rifky Ardhi (Pendidikan Geografi, 2014)
ABSTRACTThe objective of research was to find out the improvement of geographical learning outcome by applying Make a Match method with Google Earth media in basic competency of earth surface formation process in the X-b graders of MAN Ngrambe, Ngawi Regency in the school year of 2013/2014.This study employed a Classroom Action Research approach. The data sources in this study were (1) the X-b graders of MAN Ngrambe of Ngawi Regency as the subject of research, consisting of 23 students, (2) the teachers assuming geography subject in X-b grade, in which the data was obtained concerning the learning outcome of students before treatment, (3) document or archive concerning the data of the X-b graders of MAN Ngrambe of Ngawi Regency, and (4) the event concerning the application of make a match method with google earth media during the application process. Techniques of collecting data used in this study were: (1) documentation, (2) observation, and (3) geographical learning outcome test. Technique of analyzing data used was descriptive qualitative analysis.Considering the result of research, it could be concluded that the application of Make a Match learning method with Google Earth media could improve the geographical learning outcome in basic competency of earth surface formation process in the X-b graders of MAN Ngrambe, Ngawi Regency in the school year of 2013/2014. It could be seen from the increasing mean score of geographical learning outcome. Before the research, the mean score of students was 70.5. After the implementation of cycle I, the mean score increased to 74.5. The students attained the minimum passing standard (70) increased from 69.5% or 16 students. After the implementation of cycle II, the mean score increased to 79. The students achieving the minimum passing standard (70) increased to 82.6% or 19 students.  Keywords: make a match, google earth, learning outcome.